CuCe / SiO2 composite aerogel catalytic material as well as preparation method and application thereof

Through CuCe/SiO2 composite aerogel catalytic material, the preparation of microwave hydrothermal method is solved, and the temperature and cost problems of existing catalysts are solved when removing NO and CO are achieved, and the catalytic effect is achieved, which is suitable for flue gas purification. .

CN119236954AInactive Publication Date: 2025-01-03INNER MONGOLIA UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411357672.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When removing NO and CO in flue gas, existing catalysts have problems such as high operating temperature, narrow temperature window, and by-product generation. The precious metal catalysts are costly and inactivated at high temperatures, and the thermal stability of rare earth oxides is poor and selective. Limits the application of catalysts.

Method used

CuCe/SiO2 composite aerogel catalytic material is prepared by microwave hydrothermal method. SiO2 aerogel is used as a support to support Cu and Ce oxides to form nanoparticles with high specific surface area and uniform dispersion, which improves catalytic activity and stability.

Benefits of technology

It has achieved efficient catalytic conversion of CO and NO into harmless gas, has good oxygen storage capacity and cerium/copper ion coupled variable valence characteristics, is suitable for high temperature and high pressure conditions, is low cost, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236954A_ABST
    Figure CN119236954A_ABST
Patent Text Reader

Abstract

The invention provides a CuCe / SiO2 composite aerogel catalytic material as well as a preparation method and application thereof, and belongs to the technical field of flue gas denitration catalytic materials. According to the CuCe / SiO2 composite aerogel catalytic material, SiO2 aerogel is used as a carrier, and a transition metal oxide is loaded on the carrier; the transition metal oxide is an oxide of Cu and an oxide of Ce. The preparation method comprises the following steps: dissolving cerium salt and copper salt in water, then adding SiO2 aerogel, uniformly mixing, and carrying out microwave hydrothermal synthesis reaction on the obtained mixed solution to obtain a precursor material; and roasting the precursor material, so as to obtain the CuCe / SiO2 composite aerogel catalytic material. The CuCe / SiO2 composite aerogel catalytic material provided by the invention has the characteristics of uniform pore size distribution, high specific surface area, large pore volume and strong adsorption capacity, and can efficiently catalyze NO and CO to be converted into N2 and CO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flue gas denitration catalytic materials, and in particular to a CuCe / SiO2 composite aerogel catalytic material and a preparation method and application thereof. Background Art

[0002] NO not only pollutes the atmosphere, but also harms human health. NO will bind to hemoglobin in the human body, thereby affecting the ability of hemoglobin to transport oxygen. At the same time, NO can be oxidized in the air to produce NO2, which is one of the main causes of photochemical smog and acid rain. How to remove NO from industrial waste gas has become a global hot topic. Nowadays, ammonia selective catalytic reduction (NH3-SCR) has been put into practical application, but commonly used industrial catalysts such as V2O5-WO3 / TiO2 have disadvantages such as high operating temperature, narrow temperature window (300-400℃), and the production of a large amount of N2O byproducts, which limits the further development of the technology. In addition to NO, CO also exists in industrial waste gases such as sintering flue gas and automobile exhaust. Therefore, using CO as a reducing agent can remove these two harmful gases, CO and NO, at the same time, achieving the effect of killing two birds with one stone.

[0003] At present, researchers have developed many denitrification catalysts for catalyzing the reduction of NO by CO. Common catalysts for the reduction of NO by CO are divided into two types: precious metal catalysts and non-precious metal catalysts. Although precious metal catalysts have high denitrification efficiency, their high cost and deactivation at high temperatures limit their scope of application. Rare earth elements play an irreplaceable role in many fields of the national economy. CeO2, as an extremely important rare earth oxide, is widely used in many fields. CeO2 has a large specific surface area and excellent oxygen storage performance, and can store and release more active oxygen. In addition, the extremely high lattice oxygen storage capacity of CuO2 makes it an important oxygen carrier material in the fields of chemical chain combustion and chemical oxygen storage. However, both types of oxides have essential defects, such as the poor thermal stability of CeO2 and the poor selectivity of single CuO2, which makes it difficult to be directly applied in the field of catalysis. Summary of the invention

[0004] In order to solve the above-mentioned technical problem of catalytic denitrification of coal-fired flue gas, the present invention proposes a CuCe / SiO2 composite aerogel catalytic material and its preparation method and application. The present invention synthesizes CuCe / SiO2 aerogel to provide rich porosity and specific surface area, and develops a CuCe / SiO2 composite oxide aerogel catalytic material with high specific surface area, high dispersibility and high deep catalytic oxidation ability.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a CuCe / SiO2 composite aerogel catalytic material, which uses SiO2 aerogel as a carrier, and the carrier is loaded with transition metal oxides; the transition metal oxides are Cu oxides and Ce oxides.

[0007] The second technical solution of the present invention is a method for preparing the above-mentioned CuCe / SiO2 composite aerogel catalytic material, comprising the following steps:

[0008] The cerium salt and the copper salt are dissolved in water, and then SiO2 aerogel is added and mixed evenly, and the obtained mixed solution is subjected to microwave hydrothermal synthesis reaction to obtain a precursor material;

[0009] The CuCe / SiO2 composite aerogel catalytic material is obtained by calcining the precursor material.

[0010] The third technical solution of the present invention is the application of the above-mentioned CuCe / SiO2 composite aerogel catalytic material in catalyzing flue gas containing CO and NO.

[0011] A fourth technical solution of the present invention is a flue gas denitration catalyst, the raw materials of which include the above-mentioned CuCe / SiO2 composite aerogel catalytic material.

[0012] Beneficial technical effects:

[0013] The present invention adopts a microwave heating method to prepare a CuCe / SiO2 composite aerogel catalytic material, which can obtain uniformly dispersed nanoparticles, increase the specific surface area and dispersion of the catalytic material, and further improve the catalytic activity and stability. In addition, the preparation method of the present invention is simple, low-cost, and suitable for large-scale industrial production.

[0014] The invention adopts a microwave hydrothermal method to prepare a CuCe / SiO2 composite aerogel catalytic material, which has the characteristics of uniform pore size distribution, high specific surface area and large pore volume, and strong adsorption capacity.

[0015] The present invention adopts microwave heating method to prepare CuCe / SiO2 composite aerogel catalytic material, which can ensure the yield and purity of the product, is inexpensive and readily available, is non-flammable and can avoid being flammable and explosive, and is non-toxic. Its critical temperature and pressure are both low, and the requirements for equipment are not too harsh.

[0016] The CuCe / SiO2 composite aerogel catalytic material provided by the present invention has high oxygen storage capacity and cerium / copper ion coupled valence change characteristics, can efficiently catalyze the conversion of CO and NO into non-toxic and harmless CO2 and N2, and has good application prospects in the field of catalysis involving oxygen storage / release and redox cycle processes.

[0017] The present invention also provides an application of the CuCe / SiO2 composite aerogel catalytic material, which is suitable for a variety of chemical reactions. Experiments have shown that the CuCe / SiO2 composite aerogel catalytic material has high catalytic activity and stability, and can still maintain a good catalytic effect under harsh conditions such as high temperature and high pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a flow chart for preparing the CuCe / SiO2 composite aerogel catalytic material of the present invention;

[0020] Figure 2 This is a graph showing the conversion rate of NO by the CuCe / SiO2 composite aerogel catalytic material obtained in Examples 1-9 of the present invention;

[0021] Figure 3 This is a graph showing the conversion rate of CO of the CuCe / SiO2 composite aerogel catalytic material obtained in Examples 1-9 of the present invention. DETAILED DESCRIPTION

[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0027] The invention provides a CuCe / SiO2 composite aerogel catalytic material, which takes SiO2 aerogel as a carrier, and the carrier is loaded with transition metal oxides; the transition metal oxides are Cu oxides and Ce oxides.

[0028] In some embodiments of the present invention, the loading amount of Ce on the carrier is 10 wt %, and the molar ratio of Ce:Cu is 10:(1-3).

[0029] The present invention selects cerium (Ce) and copper (Cu) as catalyst components, and utilizes the synergistic effect between different components to purify coal-fired flue gas. The CuCe / SiO2 composite aerogel catalytic material is prepared by microwave heating. The present invention utilizes the high porosity and abundant acid sites of SiO2 aerogel to promote the rapid adsorption and decomposition of substrate molecules, exerting a catalytic effect, and the catalytic material can oxidize CO and NO into N2 and CO2. In addition, the present invention provides a different preparation method for aerogel catalytic materials in the prior art. Due to the different preparation methods, the aerogel structures formed are also different, which in turn affects the catalytic performance of the final catalytic material. In addition, the present invention uses the prepared silica aerogel as a carrier, omits the supercritical drying of carbon dioxide in the preparation process, and the steps are simple and easy to operate, and can be used for large-scale industrial production.

[0030] In some embodiments of the present invention, the molar ratio of the Ce element in the Ce oxide to the Cu element in the Cu oxide is 10:(1-3).

[0031] In the present invention, when the copper content is too high, the surface active sites will be reduced, thereby affecting the catalytic activity, while when the copper content is too low, the copper dispersion will be insufficient, which will also limit the catalytic activity of the catalyst. Therefore, the present invention limits the molar ratio of Ce element to Cu element to the above parameter range.

[0032] In some embodiments of the present invention, the molar ratio of the Ce element in the Ce oxide to the Cu element in the Cu oxide is 10:1, 10:2 or 10:3.

[0033] The present invention also provides a method for preparing the CuCe / SiO2 composite aerogel catalytic material, comprising the following steps:

[0034] The cerium salt and the copper salt are dissolved in water, and then SiO2 aerogel is added and mixed evenly, and the obtained mixed solution is subjected to microwave hydrothermal synthesis reaction to obtain a precursor material;

[0035] The CuCe / SiO2 composite aerogel catalytic material is obtained by calcining the precursor material.

[0036] In some embodiments of the present invention, the cerium salt is Ce(NO3)3·6H2O; the copper salt is Cu(NO3)2·3H2O.

[0037] In some embodiments of the present invention, the mass ratio of the Ce(NO3)3·6H2O to the SiO2 aerogel is 4.34:4.

[0038] In some embodiments of the present invention, in the microwave hydrothermal synthesis reaction, the microwave hydrothermal time is 15 min and the temperature is 250°C.

[0039] In the present invention, when the microwave time is short, the catalyst will not be sufficiently heat treated and the crystallinity will be poor, thereby reducing the catalytic activity of the catalyst; and when the microwave time is too long, the catalyst will be sintered, and its specific surface area will be reduced, which will also have a certain impact on the catalytic activity. In terms of temperature, when the temperature is too low, the reaction rate will be reduced, resulting in incomplete reaction and affecting its catalytic performance. When the temperature is too high, although the reaction rate is accelerated to a certain extent, its grain growth is too fast, which will reduce the specific surface area and the number of active sites of the catalyst. Therefore, the present invention limits the parameters of microwave hydrothermal synthesis to the above range.

[0040] In some embodiments of the present invention, after the microwave hydrothermal synthesis reaction is completed, the step of drying the obtained product is further included; the drying temperature is 80°C.

[0041] In some embodiments of the present invention, the calcination temperature is 500° C.-700° C., and the calcination time is 4 hours.

[0042] The present invention also provides the use of the CuCe / SiO2 composite aerogel catalytic material in catalyzing flue gas containing CO and NO.

[0043] The present invention also provides a flue gas denitration catalyst, the raw materials of which include the CuCe / SiO2 composite aerogel catalytic material.

[0044] In order to better understand the present invention, the following examples are used to further illustrate the content of the present invention, but the content of the present invention is not limited to the following examples. The preparation process of CuCe / SiO2 composite aerogel catalytic material is as follows Figure 1 shown.

[0045] Unless otherwise specified, the raw materials and reagents used in the examples can be obtained through commercial sources.

[0046] Example 1

[0047] This embodiment provides a CuCe / SiO2 composite aerogel catalytic material, and the preparation method is as follows:

[0048] Step 1. Accurately weigh 4.34g of cerium nitrate and 0.241g of copper nitrate and dissolve them in 60ml of deionized water, stirring continuously until completely dissolved. Accurately weigh 4g of SiO2 aerogel material and add it to the above solution, then place it in a microwave oven and heat it at 250℃ for 15min. The nitrate in the solution precipitates and is loaded on the SiO2 aerogel, then placed in a forced air oven and dried at 80℃ to obtain a precursor;

[0049] Step 2. Calcine the prepared precursor at 500° C. for 4 h under an inert atmosphere to decompose the nitrate into oxides to form a CuCe composite oxide catalyst, namely, a CuCe / SiO2 composite aerogel catalytic material.

[0050] In the CuCe / SiO2 composite aerogel catalytic material, nCe:nCu=10:1.

[0051] Example 2

[0052] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 1, except that the calcination temperature is 600°C.

[0053] Example 3

[0054] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 1, except that the calcination temperature is 700°C.

[0055] Example 4

[0056] This embodiment provides a CuCe / SiO2 composite aerogel catalytic material, and the preparation method is as follows:

[0057] Step 1. Accurately weigh 4.34g of cerium nitrate and 0.428g of copper nitrate and dissolve them in 60ml of deionized water, stirring continuously until completely dissolved. Accurately weigh 4g of SiO2 aerogel material and add it to the above solution, then place it in a microwave oven and heat it at 250℃ for 15min. The nitrate in the solution precipitates and is loaded on the SiO2 aerogel, then placed in a forced air oven and dried at 80℃ to obtain a precursor;

[0058] Step 2. Calcine the prepared precursor at 500° C. for 4 h under an inert atmosphere to decompose the nitrate into oxides to form a CuCe composite oxide catalyst, namely, a CuCe / SiO2 composite aerogel catalytic material.

[0059] In the CuCe / SiO2 composite aerogel catalytic material, nCe:nCu=10:2.

[0060] Example 5

[0061] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 4, except that the calcination temperature is 600°C.

[0062] Example 6

[0063] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 4, except that the calcination temperature is 700°C.

[0064] Example 7

[0065] This embodiment provides a CuCe / SiO2 composite aerogel catalytic material, and the preparation method is as follows:

[0066] Step 1. Accurately weigh 4.34g of cerium nitrate and 0.723g of copper nitrate and dissolve them in 60ml of deionized water, stirring continuously until completely dissolved. Accurately weigh 4g of SiO2 aerogel material and add it to the above solution, then place it in a microwave oven and heat it at 250℃ for 15min. The nitrate in the solution precipitates and is loaded on the SiO2 aerogel, then placed in a forced air oven and dried at 80℃ to obtain a precursor;

[0067] Step 2. Calcine the prepared precursor at 500° C. for 4 h under an inert atmosphere to decompose the nitrate into oxides to form a CuCe composite oxide catalyst, namely, a CuCe / SiO2 composite aerogel catalytic material.

[0068] In the CuCe / SiO2 composite aerogel catalytic material, nCe:nCu=10:3.

[0069] Example 8

[0070] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 7, except that the calcination temperature is 600°C.

[0071] Example 9

[0072] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this embodiment is the same as that in Example 7, except that the calcination temperature is 700°C.

[0073] The conversion rates of the CuCe / SiO2 composite aerogel catalytic materials prepared in Examples 1-9 to CO and NO were tested using the following specific testing methods:

[0074] The catalyst was tested for denitrification activity using a fixed bed. The experimental instrument consists of a gas distribution box, a vertical furnace, a Fourier infrared flue gas analyzer and a computer acquisition system. The total gas flow rate of the gas distribution box is 500ml / min, the air velocity is 8000h-1, 2000ppmCO and 500ppmNO (carbon-nitrogen ratio is 4:1) are introduced, and N2 is used as a balance gas. The temperature selected in the experiment is 200-500℃, and the heating rate of the vertical tube furnace is 10℃ / min. After the gas is prepared, the tube furnace is heated to the target temperature, and the NO concentration at this time is recorded, recorded as (NO)in. Then 0.5g of sample is loaded into the quartz tube, and then the quartz tube is placed in the vertical furnace. The Fourier infrared spectroscopy flue gas analyzer and the computer acquisition system are used to measure the outlet gas composition in real time. When the gas concentration reaches stability, the NO concentration at this time is recorded, recorded as (NO)out.

[0075] Calculate the catalyst denitrification rate:

[0076] Depend on Figure 2 It can be seen that the catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:2 has the best catalytic effect after being treated at 600°C (ie, Example 5). The catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:1 (ie, Example 2) has a NO conversion rate of 46.5% at 200°C. When the temperature is increased to 400°C, the NO conversion rate reaches the highest, which is 77%. The NO conversion rate increases fastest at 250-350°C. The catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:2 (ie, Example 2) has a NO conversion rate of 46.5% at 200°C. When the temperature is increased to 400°C, the NO conversion rate reaches the highest, which is 77%. The NO conversion rate increases fastest at 250-350°C. The NO conversion rate of the catalyst of Example 5) at 200°C is 50.3%. When the temperature is increased to 400°C, the NO conversion rate reaches the highest, which is 91%. The NO conversion rate increases fastest at 250-350°C; the NO conversion rate of the catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:3 (i.e., Example 8) at 200°C is 33%. When the temperature is increased to 400°C, the NO conversion rate reaches the highest, which is 62.5%. The NO conversion rate increases fastest at 250-350°C.

[0077] Depend on Figure 3 It can be seen that the catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:2 has the best catalytic effect after being treated at 600°C (i.e., Example 5). The catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:1 (i.e., Example 2) has a CO conversion rate of 80% at 200°C. When the temperature is increased to 400°C, the CO conversion rate reaches the highest, which is 83%. The CO conversion rates are all between 80% and 85%, and are in a stable state within the temperature range of 200 to 500°C. The CO conversion rate of the catalyst with a copper-cerium doping ratio of n(Ce):n(Cu)=10:3 (i.e., Example 8) was 68% at 200°C. When the temperature was increased to 400°C, the CO conversion rate reached a maximum of 72%, and was stable in the temperature range of 200 to 500°C.

[0078] Comparative Example 1

[0079] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this comparative example is the same as that in Example 1, except that the calcination temperature is 400°C.

[0080] The calcination temperature is too low, which leads to the instability of the pore structure of the aerogel, affecting its mechanical properties and durability. The conversion rate of CO and NO by the CuCe / SiO2 composite aerogel catalytic material was tested, and the results showed that the conversion rates of CO and NO were greatly reduced (the conversion rate of CO was 73%, and the conversion rate of NO was 76%).

[0081] Comparative Example 2

[0082] The preparation method of the CuCe / SiO2 composite aerogel catalytic material provided in this comparative example is the same as that in Example 1, except that the calcination temperature is 1000°C.

[0083] The calcination temperature is too high, which causes a significant change in the pore structure of the aerogel and changes its crystal form, thus affecting its catalytic performance, reducing its compressive strength and fracture resistance, and reducing its thermal stability, making it easy to decompose or sinter at high temperatures. The conversion rate of CO and NO by the CuCe / SiO2 composite aerogel catalytic material was tested, and the results showed that the conversion rates of CO and NO were greatly reduced (the conversion rate of CO was 64%, and the conversion rate of NO was 68%).

[0084] Comparative Example 3

[0085] This comparative example provides a CeZr / SiO2 composite aerogel catalytic material, and the preparation method is the same as that of Example 1, except that 0.241 g of copper nitrate is replaced by 3.66 g of zirconium nitrate.

[0086] The denitration activity of CeZr / SiO2 composite aerogel catalytic material was tested using a fixed bed, and the test method was referred to the test method of CuCe / SiO2 composite aerogel catalytic material in Examples 1-9. The results showed that the conversion rate of CO to CeZr / SiO2 composite aerogel catalytic material was 57%, and the conversion rate of NO to CeZr / SiO2 composite aerogel catalytic material was 63%.

[0087] Comparative Example 4

[0088] This comparative example provides a CuCe composite aerogel catalytic material, and the preparation method is as follows:

[0089] Step 1. Dissolve 0.428 g of copper nitrate and 4.34 g of cerium nitrate in 30 mL of a mixed solution of ethanol and water in a volume ratio of 1:1, add 3 mL of glacial acetic acid and 2.25 mL of formamide, and stir magnetically to obtain a mixed solution;

[0090] Step 2. Place the obtained mixed solution in an oven at 80°C to form a gel, and soak the wet gel in anhydrous ethanol for 6 times, each time for 12 hours. After it is completely gelled and the water in the skeleton is completely replaced, place the wet gel in a reactor and perform supercritical drying to obtain a block aerogel. Place the block aerogel sample in a muffle furnace at 400°C for heat treatment for 2 hours, with a heating rate of 5°C / min, to obtain a CuCe composite aerogel catalytic material.

[0091] Comparative Example 4 uses a supercritical drying preparation method to prepare aerogel with copper cerium as the substrate, while the present invention uses a formed industrial aerogel as a carrier to load the active elements on the carrier surface. Loading the active components on the aerogel carrier helps to disperse them more evenly, while saving costs to a certain extent, and can be used for large-scale industrial production. Its catalytic performance is improved by 7%-10% compared with that after supercritical drying.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A CuCe / SiO2 composite aerogel catalytic material, characterized in that: SiO2 aerogel is used as a carrier, and transition metal oxides are loaded on the carrier; the transition metal oxides are Cu oxides and Ce oxides.

2. The CuCe / SiO2 composite aerogel catalytic material according to claim 1, characterized in that: The molar ratio of the Ce element in the Ce oxide to the Cu element in the Cu oxide is 10:(1-3).

3. A method for preparing the CuCe / SiO2 composite aerogel catalytic material according to claim 1 or 2, characterized in that: The following steps are involved: The cerium salt and the copper salt are dissolved in water, and then SiO2 aerogel is added and mixed evenly, and the obtained mixed solution is subjected to microwave hydrothermal synthesis reaction to obtain a precursor material; The CuCe / SiO2 composite aerogel catalytic material is obtained by calcining the precursor material.

4. The method for preparing the CuCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: The cerium salt is Ce(NO3)3·6H2O; the copper salt is Cu(NO3)2·3H2O.

5. The method for preparing the CuCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: In the microwave hydrothermal synthesis reaction, the microwave hydrothermal time is 15 minutes and the temperature is 250°C.

6. The method for preparing the CuCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: After the microwave hydrothermal synthesis reaction is completed, the step of drying the obtained product is also included; the drying temperature is 80°C.

7. The method for preparing the CuCe / SiO2 composite aerogel catalytic material according to claim 3, characterized in that: The calcination temperature is 500° C.-700° C., and the calcination time is 4 hours.

8. Use of the CuCe / SiO2 composite aerogel catalytic material according to claim 1 or 2 in catalyzing flue gas containing CO and NO.

9. A flue gas denitration catalyst, characterized in that: The raw material includes the CuCe / SiO2 composite aerogel catalytic material according to claim 1 or 2.

Citation Information

Patent Citations

  • Low-temperature denitrified CeO2-CuO catalyst and preparation method and applications thereof

    CN102989465A

  • Method for directly decomposing NO by microwave catalysis and catalyst

    CN106345292A

  • Preparation method of CuO-CeO2 supported catalyst and application of CuO-CeO2 supported catalyst in anaerobic elimination of NOx and CO in tail gas

    CN112844394A

  • Preparation method and application of NO and CO integrated removal catalyst in oxygen-enriched environment

    CN118663310A